Calpain inhibitor-1 reduces renal ischemia/reperfusion injury in the rat - Chatterjee, PK (2015)
Background. Activation of the cysteine protease calpain has been implicated in renal ischemia/reperfusion (I/R) injury. The aim of this study was to investigate the effects of calpain inhibitor-1 (Cal I-1) in an in vivo model of renal I/R injury. Methods. Male Wistar rats were administered (Cal I-1 (10 mg/kg, IP) 30 minutes before undergoing bilateral renal ischemia (45 minutes) followed by reperfusion (6 hours). Plasma concentrations of urea, creatinine, Na+, gamma -glutamyl transferase (gamma GT), aspartate aminotransferase (AST) and urinary Na+ glutathione S-transferase (GST), and N-acetyl-beta -D-glucosaminidase (NAG) were measured for the assessment of renal dysfunction and I/R injury. Creatinine clearance (C-Cr) and fractional excretion of Na+ (FENa) were used as indicators of glomerular and tubular function, respectively. Kidney myeloperoxidase (MPO) activity and malondialdehyde (MI)A) levels were measured for assessment of neutrophil infiltration and lipid peroxidation, respectively. Renal sections were used for histologic grading of renal injury and for immunohistochemical localization of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Results. Cal I-1 significantly reduced I/R-mediated increases in urea, creatinine, gamma GT, AST, NAG, and FENa and significantly improved C-Cr. Cal I-1 also significantly reduced kidney MPO activity and MDA levels. Cal I-1 also reduced histologic evidence of I/R-mediated renal damage and caused a substantial reduction in the expression of iNOS and COX-2, both of which involve activation of nuclear factor-kappaB (NF-kappaB). Conclusions. These results suggest that Cal I-1 reduces the renal dysfunction and injury associated with I/R of the kidney. We suggest that the mechanism could involve the inhibition of I/R-mediated activation of NF-kappaB.